Medical device cybersecurity for engineers and manufacturers - Wirth, Axel (Security strategist); Gates, Christopher; Smith, Jason (Artech House, 2020)
Cybersecurity for medical devices is no longer optional. We must not allow sensationalism or headlines to drive the discussion… Nevertheless, we must proceed with urgency. In the end, this is about preventing patient harm and preserving patient trust.   A comprehensive guide to medical device secure lifecycle management, this is a book for engineers, managers, and regulatory specialists. Readers gain insight into the security aspects of every phase of the product lifecycle, including concept, design, implementation, supply chain, manufacturing, postmarket surveillance, maintenance, updates, and end of life.   Learn how to mitigate or completely avoid common cybersecurity vulnerabilities introduced during development and production. Grow your awareness of cybersecurity development topics ranging from high-level concepts to practical solutions and tools. Get insight into emerging regulatory and customer expectations. Uncover how to minimize schedule impacts and accelerate time-to-market while still accomplishing the main goal: reducing patient and business exposure to cybersecurity risks.   Medical Device Cybersecurity for Engineers and Manufacturers is designed to help all stakeholders lead the charge to a better medical device security posture and improve the resilience of our medical device ecosystem
Keywords: Medical instruments and apparatus industry.; Medical instruments and apparatus -- Safety regulations.; Computer security.; elektronické knihy; electronic books